2019
DOI: 10.1111/hae.13889
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding assessment in haemophilia carriers—High rates of bleeding after surgical abortion and intrauterine device placement: A multicentre study in China

Abstract: Introduction: An increased bleeding tendency has been shown in female haemophilia carriers compared to healthy females. Bleeding assessment tools (BATs) have mainly been performed in western cultures. It is unclear how they perform in populations with different healthcare, health/wellness concepts and awareness, as well as family planning practices. Aim: To (a) describe and compare the bleeding symptoms in carriers with healthy females, particularly for bleeding after surgical abortion and intrauterine device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…There were also no significant differences in factor levels between carriers with high (≥4) and low (<4) BAT scores. In the Chinese cohort, investigators did not find any significant correlation between ISTH‐BAT scores and factor levels 16 . All of these cohorts did provide evidence that even carriers with normal baseline FVIII or FIX levels can have abnormal BAT scores, and at an increased frequency compared to the general population.…”
Section: Bleeding In Women and Girls With Haemophilia – Epidemiology Anmentioning
confidence: 90%
See 1 more Smart Citation
“…There were also no significant differences in factor levels between carriers with high (≥4) and low (<4) BAT scores. In the Chinese cohort, investigators did not find any significant correlation between ISTH‐BAT scores and factor levels 16 . All of these cohorts did provide evidence that even carriers with normal baseline FVIII or FIX levels can have abnormal BAT scores, and at an increased frequency compared to the general population.…”
Section: Bleeding In Women and Girls With Haemophilia – Epidemiology Anmentioning
confidence: 90%
“…Studies from Belgium, Sweden and the United States have shown that cutaneous bleeding, epistaxis and postsurgical bleeding are also commonly reported by WGWH 13‐15 . In a cohort of 145 carriers in China (accompanying male relatives rather than referred for clinical management themselves), participants completed a modified ISTH‐BAT score, which included additional questions regarding bleeding after intrauterine device placement and surgical abortion 16 . Carriers had higher BAT scores than controls (3 vs 1, P <.001), and also reported high rates of excessive bleeding after intrauterine device placement (36%, 21/58) and surgical abortion (41%, 33/80).…”
Section: Bleeding In Women and Girls With Haemophilia – Epidemiology Anmentioning
confidence: 99%
“…This should provide a more robust data set going forward. Finally, our analysis portrays a subset of haemophilia carriers residing in the United States and may not be applicable to other areas of the world 13,23 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 The common misconception by patients and health-care providers (HCPs) that all HCs are asymptomatic is shifting, due to an increasing body of evidence that contradicts this assumption. [3][4][5][6][7] The term HC, and its associated connotations, such as obligate and possible carriers, has hampered diagnosis, management, and research. 8,9 For each man with hemophilia, 1.6 female carriers can be identified.…”
Section: Backg Round and R Ationalementioning
confidence: 99%
“…Due to lyonization, a random interindividual X‐linked inactivation process, median plasma factor VIII/IX (FVIII/IX) levels of hemophilia carriers (HCs) are 0.60 IU/ml (range 0.05–2.19), and 28% have factor levels <0.40 IU/ml, which would be defined as hemophilia according to the World Federation of Hemophilia (WFH) 1,2 . The common misconception by patients and health‐care providers (HCPs) that all HCs are asymptomatic is shifting, due to an increasing body of evidence that contradicts this assumption 3–7 . The term HC, and its associated connotations, such as obligate and possible carriers, has hampered diagnosis, management, and research 8,9 …”
Section: Background and Rationalementioning
confidence: 99%